PENENTUAN LOKASI POTENSIAL RELOKASI PERMUKIMAN RAWAN BANJIR DI DAS KURANJI, KOTA PADANG - Salsabilla Putri Nasywa; Iswandi Umar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Flood is one of the most frequent hydrometeorological disasters in Indonesia and causes significant damage to settlements, infrastructure, and community livelihoods. The Kuranji Watershed (DAS Kuranji) in Padang City is highly vulnerable to recurrent flooding, making the identification of safe and sustainable relocation areas essential. This study aimed to determine potential relocation sites for flood-prone settlements based on land suitability evaluation and to assess their sustainability from economic, social, environmental, and infrastructure perspectives. A quantitative spatial approach was employed by integrating weighted overlay analysis using Geographic Information Systems (GIS) and Multidimensional Scaling (MDS) through the Rapid Appraisal for Sustainability (RAPS) method. Land suitability analysis was conducted using six physical parameters: slope, flood frequency, drainage, gravel content, soil texture, and effective soil depth. The resulting land suitability map was overlaid with land cover and spatial planning (RTRW) maps to identify feasible relocation areas. The results showed that suitable land (S2) dominated the Kuranji Watershed, covering 17,615.75 ha (80.52%), followed by marginally suitable land (S3) of 2,728.19 ha (12.47%) and highly suitable land (S1) of 1,465.41 ha (6.70%). The integration of land suitability, land cover, and RTRW maps produced several potential relocation areas that comply with land use and spatial planning regulations. Sustainability assessment generated an index of 56.83, indicating a moderately sustainable category. These findings provide a scientific basis for supporting flood risk reduction strategies and sustainable settlement relocation planning in the Kuranji Watershed, Padang City. Keywords: Flood relocation, Land suitability, Sustainability assessment